THE EXISTENCE OF PROPHETIC LAW IN THE DEVELOPMENT OF CHILDREN'S LAW IN INDONESIA - Bambang Sukoco (INFOKUM, 2019)
This paper aims to 1). Describe and provide analysis of the prophetic legal paradigm and the development of children's law; 2) Describe and analyze the existence of prophetic law in the development of child law in Indonesia. This research is a normative legal research conducted by researching literature materials or secondary data. The approach used is a legislative approach and a conceptual approach. The international convention on the rights of the child has formulated universal principles and legal norms regarding the legal protection of children. Positive laws that apply in Indonesia tend to only regulate aspects such as child custody, recognition, and legalization. In fact, the development of children's law in the future does not only talk about administrative aspects but must be comprehensive. Islamic law has a deeper perspective compared to conventional law in general. The prophetic law paradigm can be one of the approaches in the development of child law in Indonesia that can integrate the protection of children from the womb to adulthood.